Voluntary Euthanasia: A Utilitarian Perspective - Singer, Peter (Bioethics, 2003)
Belgium legalised voluntary euthanasia in 2002, thus ending the long isolation of the Netherlands as the only country in which doctors could openly give lethal injections to patients who have requested help in dying. Meanwhile in Oregon, in the United States, doctors may prescribe drugs for terminally ill patients, who can use them to end their life – if they are able to swallow and digest them. But despite President Bush's oft-repeated statements that his philosophy is to ‘trust individuals to make the right decisions’ and his opposition to ‘distant bureaucracies’, his administration is doing its best to prevent Oregonians acting in accordance with a law that its voters have twice ratified. The situation regarding voluntary euthanasia around the world is therefore very much in flux. This essay reviews ethical arguments regarding voluntary euthanasia and physician-assisted suicide from a utilitarian perspective. I shall begin by asking why it is normally wrong to kill an innocent person, and whether these reasons apply to aiding a person who, when rational and competent, asks to be killed or given the means to commit suicide. Then I shall consider more specific utilitarian arguments for and against permitting voluntary euthanasia.